A Voxel-Wise Meta-Analysis of Gray Matter Abnormalities in Essential Tremor - Han, Qing; Hou, Yanbing; Shang, Huifang (Frontiers in Neurology, 2018)
Objective: To identify the consistent gray matter (GM) volume changes from the whole brain voxel-based morphometry (VBM) studies on essential tremor (ET). Methods: The whole brain VBM studies comparing ET patients and healthy controls (HCs) were systematically searched in the PubMed, Embase and Web of Science from January 2000 to December 2017. Coordinates with significant differences in regional GM volume between ET patients and HCs were extracted from included studies and the meta-analysis was performed using effect size-based signed differential mapping (ES-SDM). Results: A total of ten studies with 241 ET patients and 213 HCs were included in the meta-analysis. The consistent GM volume reduction was detected in the left precuneus extending to the left posterior cingulate gyrus. The subgroup meta-analysis which included studies performed on a 3.0 T scanner revealed significant GM volume increases in the bilateral frontal lobes, bilateral temporal lobes, left insula, left striatum and left pons, but obvious publication biases of these findings were detected through funnel plots and Egger’s tests. Conclusions: The consistent result of our meta-analysis showed a structural damage in the left precuneus extending to the left posterior cingulate gyrus, which possibly played a role in the cognitive dysfunction and depression in ET patients. It might enhance our understanding of the pathophysiological mechanisms underlying ET.